“Direct me, I beseech you, to Carcosa”: Literature, retranslation, and interference - Davi S. Gonçalves (Ilha do Desterro)
This research delineates an interface between literature, plagiarism, and retranslation – having Jorge Luis Borges’ (1979) idea of creative infidelity as main theoretical framework – based on my own principles and experience as a literary translator. More specifically, I use the software WCopyFind for comparing my retranslation of “An Inhabitant of Carcosa” (Bierce, 1886) into Brazilian Portuguese (2015) with both the original and João Reis’ previous translation into European Portuguese (2010) – bearing in mind that, before publishing my translation, I have also gone through the latter. Reflecting upon retranslation, translation, and literature, I get to the conclusion that no personal choice is devoid of external influences – especially in what regards the former. Variation is nonetheless inevitable, for texts are not formed only by words, but also by what surrounds them. The discursive strength of translation, therefore, resides in the troposphere of meaning, above what is written on the surface of a text.